Incidencia de los armónicos en la red de distribución eléctrica causada por la inclusión de vehículos eléctricos - Hernández Sánchez, Diego Rubén (2018)
Nowadays, the inclusion of electric vehicles in the automotive market has been gradually introduced for reasons such as environmental friendliness, a more efficient engine, among others; and regarding to the increase in the number of automobiles, it is necessary to know the effect they produce on electricity networks, since being nonlinear loads this equipment emits a significant amount of harmonics distortion, which is why this document presents an analysis of the effect of the harmonics in the electrical distribution network as a consequence of the insertion of electric vehicles, for purposes of the study, the analysis was carried out by the mathematical tool called Hilbert-Huang Transform. First, a reconstruction of the electrical signal with the voltage and current data obtained from the electrical vehicle charge which in this case was a Renault Twizy was completed, later a statistical analysis was done to determine the probable density and the probability of occurrence of the events of harmonic distortion, the Empirical Mode Decomposition Method (EMD) was also used, and consists of decomposing any temporal signal into a series of functions that are clearly oscillating called Intrinsic Mode Functions (IMF). Then with this the instantaneous frequency spectrum of the initial series is obtained by applying the Hilbert transform, thus being able to perform the analysis in the time-frequency domain of the harmonics produced by the electric vehicle, it is important to emphasize that the Fourier Transform served as support for this analysis and to compare the benefits that one relationship has to the other.